A review of the species of Crenicichla (Teleostei: Cichlidae) from the Atlantic coastal rivers of southeastern Brazil from Bahia to Rio Grande do Sul States, with descriptions of three new species - Kullander,Sven O. (2006)
Six species of Crenicichla, three of which are new, are recognized from the Atlantic coastal rivers of souhteastern Brazil from the state of Bahia south to the state of Rio Grande do Sul: C. mucuryna (upper rio Mucuri, Minas Gerais), C. lacustris (from the rio Paraíba do Sul north to the rio Buranhem, Bahia), C. iguapina, new species (rio Ribeira de Iguape), C. tingui, new species (from the rio Itapocu to the rio Nhundiaquara drainage), C. maculata, new species (lagoa dos Quadros, rio Maquiné, Rio Grande do Sul to rio Itapocu, Santa Catarina drainages), and Crenicichla punctata (laguna dos Patos basin). Crenicichla biocellata is a synonym of C. lacustris; and also a secondary homonym of Sparus biocellatus, a synonym of C. saxatilis. Crenicichla dorsocellata is also a synonym of C. lacustris.